more from E.J. Lemmon

### Single Idea 9525

#### [catalogued under 4. Formal Logic / B. Propositional Logic PL / 2. Tools of Propositional Logic / d. Basic theorems of PL]

Full Idea

The proof that P→Q -||- ¬(P ∧ ¬Q) is useful for enabling us to change conditionals into negated conjunctions

Gist of Idea

We can change conditionals into negated conjunctions with P→Q -||- ¬(P ∧ ¬Q)

Source

E.J. Lemmon (Beginning Logic [1965], 2.2)

Book Reference

Lemmon,E.J.: 'Beginning Logic' [Nelson 1979], p.62